2023
DOI: 10.1136/gutjnl-2022-328364
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PPAR-gamma counteracts tumour adaptation to immune-checkpoint blockade in hepatocellular carcinoma

Abstract: ObjectiveTherapy-induced tumour microenvironment (TME) remodelling poses a major hurdle for cancer cure. As the majority of patients with hepatocellular carcinoma (HCC) exhibits primary or acquired resistance to antiprogrammed cell death (ligand)-1 (anti-PD-[L]1) therapies, we aimed to investigate the mechanisms underlying tumour adaptation to immune-checkpoint targeting.DesignTwo immunotherapy-resistant HCC models were generated by serial orthotopic implantation of HCC cells through anti-PD-L1-treated syngene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 55 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…PPARγ is the most extensively studied subtype, and its aberrantly high expression in HCC is associated with metabolic dysregulation and tumour progression 32 . Moreover, since PPARγ overexpression plays a potential role in tumour immune escape, simultaneous inhibition of PPARγ and immune checkpoints can reshape the immune landscape of liver tumours, and overcome resistance to immune checkpoint blockers 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARγ is the most extensively studied subtype, and its aberrantly high expression in HCC is associated with metabolic dysregulation and tumour progression 32 . Moreover, since PPARγ overexpression plays a potential role in tumour immune escape, simultaneous inhibition of PPARγ and immune checkpoints can reshape the immune landscape of liver tumours, and overcome resistance to immune checkpoint blockers 33 …”
Section: Discussionmentioning
confidence: 99%
“… 32 Moreover, since PPARγ overexpression plays a potential role in tumour immune escape, simultaneous inhibition of PPARγ and immune checkpoints can reshape the immune landscape of liver tumours, and overcome resistance to immune checkpoint blockers. 33 …”
Section: Discussionmentioning
confidence: 99%
“…This investigation did not observe any changes in PPAR expression that were induced by GRK4. It was revealed that GRK4 and PPARs are significant regulators of hypertension and HCC [ 6 , 15 , [29] , [30] , [31] , [32] ]. Although there has been no evidence that GRK4 impacts the PPAR, it was discovered that GRK2, a member of the GRK family, might be the cause of hypertension due to overexpression and PPAR downregulation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent international retrospective real‐world study comparing atezolizumab plus bevacizumab vs. anti‐VEGF lenvatinib or sorafenib as the first‐line treatment for unresectable HCC confirmed that treatment with lenvatinib was significantly associated with longer overall survival (hazard ratio [HR], 0.46) and progression‐free survival (HR, 0.55) in the NAFL/NASH subgroup, although there was no difference in patients with non‐NAFL/NASH 25 . Given that NAFLD‐HCC may be characterized by distinct molecular features as described below, metabolism‐mediating drugs such as metformin and a selective peroxisome proliferator‐activated receptor‐gamma (PPAR‐γ) antagonist may restore anti‐PD‐1 treatment efficacy in NASH by rescuing dysfunctional CD8 T cells 35,36 …”
Section: Fibrosis‐independent Hepatocarcinogenesis From Nafldmentioning
confidence: 99%